2012
DOI: 10.1097/ta.0b013e31824d0f70
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of critical care-related complications in colectomy patients using the National Surgical Quality Improvement Program

Abstract: Complications requiring ICU care represent a significant morbidity in the colectomy patient population. Frailty index seems to be an important predictor of ICU-level complications and death, and laparoscopy seems to be protective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
107
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(117 citation statements)
references
References 16 publications
7
107
0
3
Order By: Relevance
“…Most studies were observational (23 of 35) with a total of 1 153 684 patients available for the analysis. Cohorts were composed of patients undergoing lower gastrointestinal (GI) surgery (10 studies), upper GI surgery (6), mixed GI surgery (4), gynaecological surgery (6), urological surgery (4) and mixed abdominal surgery (6) ( Table  1)1 12, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies were observational (23 of 35) with a total of 1 153 684 patients available for the analysis. Cohorts were composed of patients undergoing lower gastrointestinal (GI) surgery (10 studies), upper GI surgery (6), mixed GI surgery (4), gynaecological surgery (6), urological surgery (4) and mixed abdominal surgery (6) ( Table  1)1 12, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of frail patients ranged from 0·5 to 67·2 per cent. Most surgical procedures were performed for cancer; only four studies25 28, 29 41 had fewer than half of the patients without malignancy.…”
Section: Resultsmentioning
confidence: 99%
“…6,7 Frailty has been utilized to analyze multiple postoperative complications, including mortality. 8,9 However, there is insufficient literature regarding the impact of unplanned reintubation in the elderly population.…”
Section: Introductionmentioning
confidence: 99%
“…This effect was more pronounced when the relative surgical risk was low, the converse of which the researchers confirmed in a second study of patients undergoing very complex surgery, in whom complications and mortality were less well correlated with frailty [56]. Perhaps of greater clinical relevance, when the researchers analysed data from 58 000 patients undergoing open and laparo-scopic colectomy, they found that the proportion of patients experiencing complications requiring intensive care admission correlated with increases in the same modified 11-point Frailty Index [57]; laparoscopic colectomy was associated with lower complication rates among frail patients.…”
Section: Peri-operative Implicationsmentioning
confidence: 48%